2013
DOI: 10.1016/j.imbio.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mutants of a highly cross-reactive calcium-binding protein from Brassica pollen for allergen-specific immunotherapy

Abstract: The major turnip (Brassica rapa) pollen allergen, belongs to a family of calcium-binding proteins (i.e., two EF-hand proteins), which occur as highly cross-reactive allergens in pollen of weeds, grasses and trees. In this study, the IgE binding capacity and allergenic activity of three recombinant allergen variants containing mutations in their calcium-binding sites were analyzed in sensitized patients with the aim to identify the most suitable hypoallergenic molecule for specific immunotherapy.Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A similar strategy was used for calcium-binding proteins from pollen. 42,43 In conclusion, our structural data show that the Ca 21 binding site and the region around V34 are important for the stabilization of the cod parvalbumin structure. Allergy-inducing IgE antibodies are directed against specific binding sites on the native conformation of the allergen.…”
Section: Figurementioning
confidence: 58%
See 1 more Smart Citation
“…A similar strategy was used for calcium-binding proteins from pollen. 42,43 In conclusion, our structural data show that the Ca 21 binding site and the region around V34 are important for the stabilization of the cod parvalbumin structure. Allergy-inducing IgE antibodies are directed against specific binding sites on the native conformation of the allergen.…”
Section: Figurementioning
confidence: 58%
“…Swoboda and colleagues recently showed that the introduction of mutations in the Ca 2+ binding sites could generate variants that do not bind IgE antibodies from fish‐allergic patients. A similar strategy was used for calcium‐binding proteins from pollen …”
Section: Discussionmentioning
confidence: 99%
“…As described for allergic patients’ IgE antibodies, binding of mAb102.1F10 depended on the presence of protein-bound calcium. In the calcium-bound form, EF-hand allergens are supposed to expose amino acids critical for binding of antibodies on the surface of the molecule (26, 30). The binding site of mAb102.1F10 was mapped at the C-terminal portion of the molecule containing the second EF-hand.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant timothy grass pollen allergen Phl p 7 (15) was obtained from Biomay AG (Vienna, Austria). Recombinant Ole e 8 (25) from olive pollen and Bra r 1 from turnip rape pollen were expressed in Escherichia coli and purified by Nickel-affinity chromatography (26). Recombinant Che a 3 (27) from Lamb’s quarters’ pollen was expressed and purified as described (28).…”
Section: Methodsmentioning
confidence: 99%
“…IgE from other atopic/allergic individuals have a similar ArtCaM positive rate to Artemisia allergy patients ( p>0.1 ) Therefore, we assumed ArtCaM might work as a pan-allergen in allergic patients. Meanwhile, CBPs have been identified as highly conserved, immunological and clinical cross-reactivity allergenic proteins in several plants’ pollen ( 39 ). Previous research has reported that even though CBPs were only recognized in a few pollen-sensitized patients, they can exhibit stronger allergic reactions and polysensitization in allergic patients ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%